Michail Rostovtzeﬀ als Universalhistoriker - Chrustaljow, Wjatscheslaw K. (Hyperboreus, 2021)
It is well known that astonishing diversity and universality are characteristic of Michail Rostovtzeﬀ’s research work. Yet although he was a man of extraordinarily broad scholarly interests, Rostovtzeﬀ always saw himself primarily as a historian. One of the most important methodological principles by which Rostovtzeﬀ was guided throughout his academic career was a synthetic evaluation of all types of evidence, i. e. literary, epigraphic, papyrological, archaeological and numismatic. For him the main aim of historical study was the most accurate reconstruction of a historical event or phenomenon in all its diversity. On the whole, Rostovtzeﬀ remained faithful to the theoretical and methodological attitudes he took up in his youth until the end of his life, although he further developed and improved his methods over the years. In this respect, emigration from Russia did not play a pivotal role in his scholarly fate, as it is so often claimed in Western historiography.